Pendidikan Islam menuju Universitas Riset dalam Perspektif Al Qur’an - Burhanuddin, Cepi; Abdul Muid Nawawi (Rayah Al-Islam, 2026)
Current global higher education is undergoing a transformation toward the Research University model; however, in the context of Islamic education, this discourse often falls into a technocratic approach that neglects the Quranic epistemological foundations. This study aims to discuss how concepts within the Quran can serve as a basis for building and developing research universities in the global era. The method employed is qualitative library research with a philosophical-epistemological analysis approach. Data sources consist of relevant primary and secondary scientific works, analyzed using thematic and descriptive analysis techniques. The results show that the "Iqra" command in the Quran is a theological mandate for research activities that must be based on the name of Allah (bismi rabbika) to maintain a moral compass. The development of an Islamic research university can be operationalized through four pillars: dynamic knowledge production (Al-Harakah al-Jawhariyyah), publication integrity (Ittehad al-Aqil wa al-Ma’qul), innovation through creative science (Al-Hikmah), and intellectual openness (Tajaddud al-Amthal). Strategic steps include curriculum reconstruction based on Ulul Albab, strengthening a critical culture (Burhan), interdisciplinary approaches, and implementing research ethics based on Akhlakul Karimah. This study concludes that a Quran-based research university is not merely an academic institution but a form of intellectual worship and "Modern-Day Ijtihad" to realize the welfare of the people (Rahmatan lil 'Alamin).